(untitled) (Philological Studies, 2023)
The aim of this paper is to represent the life and work of those researchers – born in Aegean Macedonia, which have made a significant contribution in modern Macedonian history to the preservation of oral folklore from the Aegean part of Macedonia. Through the methods of historical, analytical and comparative research, we gain knowledge of their abilities and skills, which made and highlighted them as fruitful researchers of folklore. With their research ventures, on one hand they took the first step to preserve this folklore wealth, which until then was beyond the reach of Macedonian folklore and cultural history. On the other hand, they preserved it from oblivion.